Gross Anatomical Studies on Broncho-Pulmonary Segments of Lungs in Domestic Pig (Sus scrofa domesticus) - Srujana G; Pramod K D; Rajendranath N; Madhava R T (Indian Journal of Veterinary Anatomy, 2024)
Gross anatomical features of lungs of domestic pigs were studied in specimens procured at slaughter from twelve apparently healthy adult Indian pigs of both sexes. The lungs appeared pale pink in colour and had clear lobation in both fresh and fixed specimens. A single deep fissure in the left lung and two fissures in the right lung divided the lung into several lobes viz., cranial and caudal on left side and cranial, middle, accessory, and caudal on right side. Post fixation six pairs of lungs were partially dissected. Remaining specimens were subjected to corrosion cast studies. The right diaphragmatic lobar bronchus continued as such giving segmental bronchi on its dorsal, medial, lateral and ventral aspects. In the left lung, apical lobar bronchus gave two segmental bronchi which branched further to form two broncho-pulmonary segments, while in the diaphragmatic lobe, segmental bronchi on dorsal, lateral, ventral, and medial surfaces gave two broncho-pulmonary segments.